Leucopenia as An Early Predictor of Thrombocytopenia and Hemorrhagic Manifestations in Dengue Fever: An Observational Study (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Dengue fever is an endemic disease in Bangladesh that has shown in creasing incidence eachpassing year. Dengue has a wide range of clinical presenta tions and laboratory findings. Thrombocytopeniais a common finding in dengue-in fected patients along with other findings like leukopenia and hemorrhage in several forms. Thrombocytopenia is an indicator of disease severity andcan lead to severe bleeding manifestations. This study aims to find the association of leukopenia with thrombocytopenia and hemorrhagic manifestations. Materials and methods: This prospective observational study was conducted in a tertiary care hospital in Chattogram, Bangladesh for a period of six months. A total of 100 patients with confirmed dengue infection who fulfilled the inclusion criteria were followed from the day of admission to recovery. Clinical and laboratory findings, Total Leucocyte Count (TLC) and platelet counts were noted. Pearson’s Correlation Test was performed for correlation identification between leukopenia with thrombocytopenia and hemorrhagic manifestations in Dengue Fever. Results: Around 60.72% of the patients with bleeding manifestations had a low Platelet count (